Life-Threatening Necrotizing Pneumonia with Panton-Valentine Leukocidin-Producing, Methicillin-Sensitive Staphylococcus aureus in a Healthy Male Co-Infected with Influenza B - Sara Agnete Hjort Larsen; Kasper Kyhl; Sharmin Baig; Andreas Petersen; Marita Reginsdóttir av Steinum; Sissal Clemmensen; Elin Jensen; Torkil á Steig; Shahin Gaini (MDPI AG, 2021)
A previously healthy male was rushed into a hospital critically ill with confusion, sepsis, and acute respiratory distress syndrome only 43 h after having a normal chest X-ray and with blood samples showing only minimally elevated C-reactive protein. Two days earlier, the patient had returned to his home country, the Faroe Islands, from a 10-day work trip aboard a Scandinavian ship in Colombia. The diagnosis turned out to be an influenza B infection and necrotizing pneumonia with Panton-Valentine leukocidin (PVL)-producing methicillin-sensitive Staphylococcus aureus (MSSA). It was influenza season in Colombia but not in the Faroe Islands. The frequency of MSSA with PVL-encoding genes among pediatric infection patients is very low in the Kingdom of Denmark and Faroe Islands and very high in Colombia, and the frequency generally varies highly by region. The patient in this case now suffers severe sequelae from the infection. With this case, we would like to remind clinicians of this rare but severe condition. PVL-producing S. aureus pneumonia should be considered in critically ill, previously healthy patients, especially during influenza season and if the patient has been traveling in countries with high frequencies of PVL-producing S. aureus.